Optical fiber and optical fiber base material used therefor
The optical fiber design with a rare earth element-doped inner core and germanium/phosphorus-doped outer core addresses diameter variations in the MCVD method, enhancing beam quality and reducing scattering by stabilizing additive concentrations and amplifying fundamental mode light.
Patent Information
- Application Number
- JP2021025362
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-19
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2041-02-19
AI Technical Summary
The MCVD method for manufacturing optical fibers with germanium-doped outer cores and rare earth element-doped inner cores leads to variations in the glass tube diameter, causing inconsistencies in additive concentrations and optical fiber characteristics, which results in beam quality deterioration and stimulated Raman scattering.
The optical fiber design includes an inner core doped with rare earth elements and an outer core doped with germanium and phosphorus, without rare earth elements, allowing for lower sintering temperatures and reduced glass tube diameter shrinkage, thereby stabilizing additive concentrations and suppressing beam quality deterioration and Raman scattering.
This design effectively suppresses beam quality deterioration and variations in optical fiber characteristics, even with large effective cross-sectional areas, by primarily amplifying fundamental mode light and minimizing Raman scattering.
Smart Images

Figure 0007610999000002 
Figure 0007610999000003 
Figure 0007610999000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical fiber and an optical fiber preform used therefor. [Background technology]
[0002] As one type of optical fiber, an amplifying optical fiber in which a rare earth element such as ytterbium (Yb) is doped in the core is known. In such an amplifying optical fiber, as described in the following Patent Document 1, aluminum (Al) may be co-doped to suppress crystallization of ytterbium, and phosphorus (P) may be further co-doped to suppress photodarkening. Also, an amplifying optical fiber is known in which a portion co-doped with rare earth elements, aluminum, and phosphorus is an inner core, and this inner core is tightly surrounded by an outer core doped with germanium (Ge). The following Patent Document 1 describes such an optical fiber. According to this optical fiber, light is amplified in the inner core doped with rare earth elements, and the amplification of light is suppressed in the outer core. Therefore, in this optical fiber, even when the effective cross-sectional area of light is large and high-order mode light propagates, light in the fundamental mode can be mainly amplified. Therefore, according to this optical fiber, even when the effective cross-sectional area of light is large, deterioration of beam quality can be suppressed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2020 / 203900 Summary of the Invention [Problem to be solved by the invention]
[0004] In order to manufacture the above optical fiber, the MCVD (Modified Chemical Vapor Deposition) method is sometimes used. In this case, generally, a predetermined number of germanium-doped glass layers that will become the outer core are laminated on the inner peripheral surface of a glass tube made of pure silica that will become the cladding, and then a predetermined number of rare earth element-doped glass layers that will become the inner core are laminated on the inner peripheral surface of the germanium-doped glass layers. When laminating the glass layers that will become the inner core, aluminum or phosphorus is added in addition to the rare earth element, as necessary.
[0005] When laminating the glass layers that will become the outer core, the outer surface of the glass tube needs to be heated to about 2000°C to 2050°C in order to sinter the germanium-doped glass. This heating may cause the glass tube to shrink in diameter. When the glass tube shrinks in diameter, the diameter of the glass tube is likely to vary. When the diameter of the glass tube varies, the concentration of the additive added to the glass layers that will become the outer core and the inner core tends to vary. An optical fiber obtained by drawing an optical fiber preform having such a variation in the concentration of the additive tends to have variation in characteristics. Therefore, the characteristic variation of the manufactured optical fiber is likely to occur due to the diameter shrinkage of the glass tube in the MCVD method.
[0006] Therefore, an object of the present invention is to provide an optical fiber that can suppress deterioration of beam quality and suppress variation in characteristics even when the effective cross-sectional area of light is large, and an optical fiber preform used therefor. [Means for solving the problem]
[0007] In order to achieve the above-mentioned object, the optical fiber of the present invention is characterized by comprising an inner core doped with a rare earth element, an outer core that tightly surrounds the outer peripheral surface of the inner core and is doped with germanium and phosphorus but not doped with a rare earth element, and a cladding that tightly surrounds the outer peripheral surface of the outer core.
[0008] By doping the inner core with a rare earth element and not doping the outer core with a rare earth element, even if the optical fiber has a profile in which light in a higher order mode propagates, it can mainly amplify light in a fundamental mode that has the greatest intensity at the center of the core and has no other intensity peaks, compared to an optical fiber in which rare earth elements are doped throughout the core. Therefore, even if light in a higher order mode with a large effective area propagates, the optical fiber of the present invention can mainly amplify light in the fundamental mode, and can suppress deterioration of beam quality. In addition, when light with a large effective area propagates, stimulated Raman scattering can be suppressed.
[0009] However, the sintering temperature of the glass body doped with germanium and phosphorus is lower than that of the glass body doped with germanium and not doped with phosphorus. Therefore, in the production of the optical fiber of the present invention, when laminating the outer core glass body to be the outer core on the inner peripheral surface of the glass tube to be the cladding by the MCVD method, the outer core glass body can be laminated at a lower temperature than when laminating the outer core glass body doped with germanium and not doped with phosphorus. Therefore, compared to the production of an optical fiber having an outer core doped with germanium and not doped with phosphorus, the temperature of the glass tube when laminating the outer core glass body can be lowered, and the diameter reduction of the glass tube due to heat can be suppressed. Therefore, the variation in the diameter of the glass tube can be suppressed, and the variation in the concentration of the additive added to the glass layer to be the outer core or the inner core can be suppressed. Therefore, the optical fiber of the present invention can suppress the variation in characteristics.
[0010] Also, the inner core is preferably co-doped with ytterbium and phosphorus.
[0011] By co-doping the inner core with ytterbium and phosphorus, the photodarkening phenomenon can be suppressed.
[0012] In this case, the concentration of phosphorus added to the inner core is preferably higher than the concentration of phosphorus added to the outer core.
[0013] It is known that the refractive index of the core changes before and after the drawing process in the manufacture of an optical fiber depending on its composition. This change in refractive index is due to mechanical stress occurring before and after drawing caused by the difference in viscosity due to the difference in composition between the cladding and the core. When the concentration of phosphorus added to the inner core is higher than that of the outer core as described above, the increase in the refractive index before and after drawing tends to be greater in the inner core than in the outer core, compared to when the concentration of phosphorus added to the inner core is lower than that of the outer core. This is due to the following reason. That is, compared to the viscosity of the outer core when the concentration of phosphorus is lower in the inner core than in the outer core, the viscosity of the outer core tends to be higher when the concentration of phosphorus is higher in the inner core than in the outer core. Considering the residual stress during drawing, the higher the viscosity, the faster the fiber solidifies during drawing and the easier it is to bear the tension when winding up during drawing. Therefore, in the optical fiber after drawing, the higher the viscosity area, the more tensile stress remains, and conversely, the lower the viscosity area, the more compressive stress remains. Therefore, in this case, the inner core has a relatively larger compressive stress remaining than the outer core. When a large compressive stress remains in the inner core compared to the outer core, the refractive index of the inner core increases more than that of the outer core due to the photoelastic effect. Meanwhile, when an optical fiber is fused, the residual stress tends to be alleviated near the fusion point due to heating during fusion. Therefore, the change in refractive index before and after drawing the inner core and the outer core due to the residual stress tends to be alleviated near the fusion point. As a result, the refractive index of the inner core relative to the outer core is smaller near the fusion point compared to the other parts. As a result, the effective cross-sectional area of light can be increased near the fusion point. Therefore, the occurrence of stimulated Raman scattering near the fusion point can be suppressed.
[0014] It is also preferable that the outer core is free of dopants other than germanium and phosphorus.
[0015] It is known that in the MCVD method, the reproducibility decreases as the number of dopants increases. In addition, when a third element is doped to the outer core together with germanium and phosphorus, the total amount of dopants increases, which may increase Rayleigh scattering loss due to composition fluctuation. Therefore, by not doping the outer core with dopants other than germanium and phosphorus, the optical fiber of the present invention can suppress the decrease in reproducibility when manufactured through the MCVD process, and can also suppress Rayleigh scattering loss.
[0016] The outer core may have a molar ratio of P2O5 / GeO2 of 1.21 or less.
[0017] In addition, in order to achieve the above-mentioned object, the optical fiber base material of the present invention is characterized in including an inner core glass body doped with a rare earth element, an outer core glass body that surrounds the outer peripheral surface of the inner core glass body without any gaps and that is doped with germanium and phosphorus but not doped with a rare earth element, and a cladding glass body that surrounds the outer peripheral surface of the outer core glass body without any gaps.
[0018] According to such an optical fiber preform, in the same manner as in the above description of the optical fiber, it is possible to manufacture an optical fiber in which deterioration of beam quality and stimulated Raman scattering can be suppressed and characteristic variations can be suppressed. Effect of the Invention
[0019] As described above, according to the present invention, an optical fiber capable of suppressing deterioration of beam quality and suppressing characteristic variations even when the effective cross-sectional area of light is large, and an optical fiber preform used therefor can be provided. [Brief description of the drawings]
[0020] [Figure 1] 1 is a diagram showing a cross-sectional structure perpendicular to the longitudinal direction of an optical fiber according to an embodiment of the present invention. [Diagram 2] 2 is a flow chart showing the steps of manufacturing the optical fiber shown in FIG. 1. [Diagram 3]2 is a diagram showing the structure of a cross section perpendicular to the longitudinal direction of an optical fiber preform used to manufacture the optical fiber shown in FIG. 1. [Figure 4] 1A to 1C are diagrams showing the outer core glass body lamination process. [Diagram 5] 1A to 1C are diagrams showing the inner core glass body lamination process. [Figure 6] FIG. 2 is a diagram showing a drawing process and a coating process. [Figure 7] 1 is a diagram showing the relationship between the radial distance from the central axis and the dopant concentration after the optical fiber preform produced in Experimental Example 1 is thinly stretched. FIG. [Figure 8] 1 is a diagram showing the relationship between the radial distance from the central axis of the optical fiber preform produced in Experimental Example 1 and the refractive index. [Figure 9] FIG. 4 is a diagram showing the change in the outer diameter of a glass tube in Experimental Example 1. [Figure 10] FIG. 13 is a diagram showing the outer diameter of the glass tube in Experimental Examples 9 and 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, embodiments for carrying out the optical fiber and optical fiber preform according to the present invention will be illustrated with reference to the drawings. The embodiments illustrated below are intended to facilitate understanding of the present invention, and are not intended to limit the present invention. The present invention can be modified or improved from the following embodiments without departing from the spirit of the present invention. In addition, in this specification, the dimensions of each member may be exaggerated in some cases to facilitate understanding.
[0022] FIG. 1 is a diagram showing the structure of a cross section perpendicular to the longitudinal direction of an optical fiber according to an embodiment. The optical fiber exemplified in this embodiment is a double-clad fiber in which a rare earth element is doped in the core, and is an amplifying optical fiber in which the rare earth element is excited by the propagating pumping light. As shown in FIG. 1, an optical fiber 10 mainly comprises a core 11, an inner clad 12 surrounding the core 11 without any gaps, an outer clad 13 surrounding the outer peripheral surface of the inner clad 12 without any gaps, and a coating layer 14 covering the outer clad 13. The core 11 also has an inner core 11i and an outer core 11o surrounding the inner core 11i without any gaps. The refractive index of the inner clad 12 is lower than that of the core 11, and the refractive index of the outer clad 13 is lower than that of the inner clad.
[0023] The inner core 11i is made of quartz doped with a rare earth element as a dopant. In this embodiment, the inner core 11i is further doped with aluminum (Al) and phosphorus (P) as dopants. Aluminum exists as Al2O3, and phosphorus exists as P2O5. Examples of rare earth elements include ytterbium (Yb), thulium (Tm), cerium (Ce), neodymium (Nd), europium (Eu), and erbium (Er). In this embodiment, ytterbium is doped as a rare earth element. The inner core 11i may further be doped with a dopant such as germanium that increases the refractive index, or a dopant such as fluorine (F) or boron (B) that decreases the refractive index. As long as a rare earth element is doped, the inner core 11i may not be doped with aluminum or phosphorus. However, in order to suppress crystallization of ytterbium, it is preferable to co-dope it with aluminum as described above, and it is also preferable to co-dope it with phosphorus in order to suppress photodarkening.
[0024] The outer core 11o is made of quartz doped with germanium (Ge) and phosphorus (P) as dopants. The outer core 11o is not doped with rare earth elements. Germanium exists as GeO2. It is preferable that the outer core 11o is not doped with dopants other than germanium and phosphorus. Doping the outer core 11o with dopants other than germanium and phosphorus can suppress the decrease in reproducibility in the MCVD process due to an increase in the number of types of additives, and suppress Rayleigh scattering loss. However, for the purpose of adjusting the refractive index, the outer core 11o may further be doped with dopants other than germanium and phosphorus that increase the refractive index, or dopants such as fluorine (F) and boron (B) that decrease the refractive index.
[0025] In this embodiment, the concentration of phosphorus added to the inner core 11i is preferably higher than the concentration of phosphorus added to the outer core 11o. By making the concentration of phosphorus added to the inner core 11i higher than the concentration of phosphorus added to the outer core 11o, it is possible to suppress the occurrence of stimulated Raman scattering near the fusion point when the optical fiber 10 is fused. The reason for this will be explained below. It is known that the refractive index of the core changes depending on its composition before and after the drawing process when manufacturing an optical fiber. This change in refractive index is due to mechanical stress that occurs before and after drawing due to the viscosity difference caused by the difference in composition between the cladding and the core. As described above, when the concentration of phosphorus added to the inner core 11i is higher than that added to the outer core 11o, the increase in the refractive index before and after drawing tends to be higher when the concentration of phosphorus added to the inner core 11i is lower than that added to the outer core 11o than when the concentration of phosphorus is higher in the inner core 11i than that in the outer core 11o. When considering the residual stress during drawing, the higher the viscosity, the faster the fiber solidifies during drawing and the easier it is to bear the tension when winding during drawing. Therefore, in the optical fiber after drawing, the higher the viscosity of the region, the more tensile stress remains, and conversely, the lower the viscosity of the region, the more compressive stress remains. Therefore, in this case, the inner core 11i has a relatively larger compressive stress remaining than the outer core 11o. When a large compressive stress remains in the inner core 11i compared to the outer core 11o in this way, the refractive index of the inner core 11i increases more than that of the outer core 11o due to the photoelastic effect. When the optical fiber 10 is fused, the residual stress tends to be alleviated near the fusion point due to heating during fusion. Therefore, near the fusion point, the change in refractive index between the inner core 11i and the outer core 11o before and after drawing due to the residual stress tends to be alleviated. As a result, near the fusion point, the relative refractive index of the inner core 11i to the outer core 11o becomes smaller compared to the other parts. As a result, the effective cross-sectional area of light can be increased near the fusion point. Therefore, the occurrence of stimulated Raman scattering near the fusion point can be suppressed.In this embodiment, the molar ratio of P2O5 / GeO2 in the outer core 11o is 1.21 or less, but may be outside this range.
[0026] It is preferable that the refractive index of the inner core 11i is approximately the same as that of the outer core 11o. As described above, the relative refractive index of the inner core 11i to the outer core 11o changes before and after the drawing process when manufacturing the optical fiber 10. As described above, when the concentration of phosphorus added to the inner core 11i is higher than the concentration of phosphorus added to the outer core 11o, the relative refractive index of the inner core 11i to the outer core 11o increases before and after the drawing process. Therefore, the refractive indexes of the inner core glass body that becomes the inner core 11i and the outer core glass body that becomes the outer core 11o are adjusted during the manufacturing of the preform of the optical fiber 10 so that the refractive indexes of the inner core 11i and the outer core 11o are approximately the same in the manufactured optical fiber 10.
[0027] The inner cladding 12 is made of pure silica to which no dopant is added. In this embodiment, the inner cladding 12 may be doped with a dopant such as fluorine or boron that reduces the refractive index.
[0028] The outer cladding 13 is made of resin or quartz. Examples of such resin include ultraviolet curable resin and thermosetting resin. Examples of quartz include quartz doped with a dopant such as fluorine or boron that reduces the refractive index to a value lower than that of the inner cladding 12. In this embodiment, the outer cladding 13 is made of thermosetting resin.
[0029] The coating layer 14 is made of a resin such as an ultraviolet curable resin or a thermosetting resin. When the outer cladding 13 is made of a resin, the coating layer 14 is made of an ultraviolet curable resin, a thermosetting resin, or the like that is different from the resin that constitutes the outer cladding 13. In this embodiment, the coating layer 14 is formed of a thermosetting resin that is different from the thermosetting resin that constitutes the outer cladding 13.
[0030] With the above configuration, in this embodiment, the refractive index of the outer cladding 13 is lower than the refractive index of the inner cladding 12 , which is lower than the refractive index of the core 11 .
[0031] Next, a method for producing the optical fiber 10 shown in FIG. 1 will be described.
[0032] Fig. 2 is a flowchart showing steps of a method for manufacturing the optical fiber 10. As shown in Fig. 2, the method for manufacturing the optical fiber 10 includes an outer core glass body laminating step P1, an inner core glass body laminating step P2, a collapsing step P3, a drawing step P4, and a coating step P5.
[0033] First, an optical fiber preform is manufactured by the manufacturing method of the optical fiber preform, which includes the outer core glass body laminating step P1, the inner core glass body laminating step P2, and the collapsing step P3.
[0034] Fig. 3 is a diagram showing the structure of a cross section perpendicular to the longitudinal direction of the optical fiber preform used to manufacture the optical fiber 10 shown in Fig. 1. As shown in Fig. 3, the optical fiber preform 10P has a cylindrical shape and is composed of a core glass body 11P that becomes the core 11 of the optical fiber 10, and a cladding glass body 12P that surrounds the outer peripheral surface of the core glass body 11P without any gaps and becomes the inner cladding 12 of the optical fiber 10. The core glass body 11P is also composed of an inner core glass body 11Pi that becomes the inner core 11i of the optical fiber 10, and an outer core glass body 11Po that surrounds the outer peripheral surface of the inner core glass body 11Pi without any gaps and becomes the outer core 11o of the optical fiber 10.
[0035] The inner core glass body 11Pi is made of the same material as the inner core 11i, the outer core glass body 11Po is made of the same material as the outer core 11o, and the cladding glass body 12P is made of the same material as the inner cladding 12. The ratio of the diameter of the inner core glass body 11Pi to the outer diameter of the outer core glass body 11Po is approximately the same as the ratio of the diameter of the inner core 11i of the optical fiber 10 to the outer diameter of the outer core 11o.
[0036] <Outer core glass body lamination process P1> FIG. 4 is a diagram showing the state of this process. This process is performed by the MCVD method. As shown in FIG. 4, in this process, the glass tube 12T which becomes the cladding glass body 12P is rotated around the axis and the burner BA is moved along the longitudinal direction of the glass tube 12T to heat the glass tube 12T. At this time, the raw material gas is supplied into the through hole of the glass tube 12T together with the carrier gas. In this process, the raw material gas is SiCl4, GeCl4, and POCl3. In the so-called forward traverse in which the burner BA moves from the supply side of the raw material gas to the discharge side, soot derived from the raw material gas is deposited on the discharge side of the burner BA, and the deposited soot is heated and sintered by the movement of the burner BA. In this way, the glass layer 11Lo which becomes the outer core glass body 11Po to which germanium and phosphorus are added as dopants is laminated on the inner peripheral surface of the glass tube 12T. Note that the temperature of the outer peripheral surface of the glass tube 12T in this process is, for example, 1800°C or more and 2100°C or less.
[0037] <Inner core glass body lamination process P2> FIG. 5 is a diagram showing the state of this process. This process is performed by the MCVD method. In this process, unlike the outer core glass body lamination process P1, the raw material gases are SiCl4, Yb(DPM)3, AlCl3, BBr3, and POCl3. In this process, in the forward traverse, first, SiCl4, Yb(DPM)3, and AlCl3 of the raw material gases are supplied together with carrier gas on the exhaust side of the burner BA, and soot derived from these raw material gases is deposited. Then, the burner BA is traversed again while supplying BBr3 together with carrier gas, and boron is added to the soot. Then, the burner BA is traversed again while supplying POCl3 together with carrier gas, and phosphorus is added to the soot. Then, the burner BA is traversed again, and the soot is heated and sintered by the movement of the burner BA, and a glass layer 11Li that becomes the inner core glass body 11Pi to which ytterbium, aluminum, and phosphorus are added as dopants is laminated on the inner peripheral surface of the glass layer 11Lo. In addition, it is preferable that the raw material gas is supplied so that the concentration of phosphorus added to the inner core glass body 11Pi is higher than the concentration of phosphorus added to the outer core glass body 11Po. The temperature of the outer peripheral surface of the glass tube 12T in this process is, for example, 1450°C to 1700°C in the process of depositing soot to which ytterbium and aluminum are added, 1100°C to 1600°C in the process of adding boron to the soot, 1100°C to 1600°C in the process of adding phosphorus to the soot, and 1800°C to 2100°C in the sintering process.
[0038] <Collapse process P3> Next, the glass tube 12T having the glass layers 11Lo and 11Li laminated on its inner circumferential surface is heated to collapse the through hole of the glass tube 12T. In this manner, the glass tube 12T becomes the cladding glass body 12P, the glass layer 11Lo becomes the outer core glass body 11Po, and the glass layer 11Li becomes the inner core glass body 11Pi, thereby producing the optical fiber preform 10P shown in FIG.
[0039] (Drawing process P4) Next, the obtained optical fiber preform 10P is drawn. FIG. 6 is a diagram showing this step and the next coating step. As shown in FIG. 6, in this step, the heating unit 111 of the spinning furnace 110 is heated to heat the optical fiber preform 10P placed in the prevention furnace, melt the lower end of the optical fiber preform 10P, and draw the optical fiber preform 10P. When the drawn glass comes out of the spinning furnace 110, it immediately solidifies, and the inner core glass body 11Pi becomes the inner core 11i, the outer core glass body 11Po becomes the outer core 11o, and the cladding glass body 12P becomes the inner cladding 12. As a result, the optical fiber bare wire 10N is formed, which is composed of the core 11 having the inner core 11i and the outer core 11o, and the inner cladding 12. Then, the optical fiber bare wire 10N passes through the cooling device 120 and is cooled to an appropriate temperature.
[0040] (Coating process P5) This process is performed after the drawing process P4. As shown in Fig. 6, the bare optical fiber 10N formed by the drawing process P4 passes through a first coating device 131 containing a first thermosetting resin that will become the outer cladding 13, and the outer surface of the inner cladding 12 is coated with this first thermosetting resin. The optical fiber coated with the first thermosetting resin enters a first heating furnace 132 and is heated in the first heating furnace 132. This heating hardens the first thermosetting resin, and the outer cladding 13 is formed on the outer surface of the inner cladding 12.
[0041] The optical fiber covered with the outer cladding 13 passes through a second coating device 133 containing a second thermosetting resin made of a material different from the first thermosetting resin, and the outer peripheral surface of the outer cladding 13 is covered with the second thermosetting resin. The optical fiber covered with the second thermosetting resin enters a second heating furnace 134 and is heated in the second heating furnace 134. This heating hardens the second thermosetting resin, and a coating layer 14 is formed on the outer peripheral surface of the outer cladding 13.
[0042] In this manner, the optical fiber preform 10P is drawn to produce the optical fiber 10 shown in Fig. 1. The direction of the produced optical fiber 10 is changed by a turn pulley 141, and the optical fiber 10 is taken up by a reel 142.
[0043] As described above, the optical fiber 10 of this embodiment includes an inner core 11i doped with a rare earth element, an outer core 11o that tightly surrounds the outer peripheral surface of the inner core 11i and is not doped with a rare earth element but is doped with germanium and phosphorus, and an inner cladding 12 that is a cladding that tightly surrounds the outer peripheral surface of the outer core 11o.
[0044] By doping the inner core 11i with a rare earth element and not doping the outer core 11o with a rare earth element, even if the optical fiber has a profile in which light in a higher order mode propagates, it can mainly amplify light in a fundamental mode that has the greatest intensity at the center of the core 11 and has no other intensity peaks, compared to an optical fiber in which rare earth elements are doped throughout the core 11. Therefore, the optical fiber 10 of this embodiment can mainly amplify light in the fundamental mode even when light in a higher order mode with a large effective area propagates, and can suppress deterioration of beam quality. Note that stimulated Raman scattering can be suppressed when light with a large effective area propagates.
[0045] Moreover, the sintering temperature of the glass body doped with germanium and phosphorus is lower than that of the glass body doped with germanium and not doped with phosphorus. Therefore, in the manufacture of the optical fiber 10 of this embodiment, when the glass layer 11Lo to become the outer core 11o is laminated on the inner circumferential surface of the glass tube 12T to become the inner cladding 12 by the MCVD method, the glass layer can be laminated at a lower temperature than when a glass layer doped with germanium and not doped with phosphorus is laminated. Therefore, compared to the manufacture of an optical fiber having an outer core doped with germanium and not doped with phosphorus, the temperature of the glass tube 12T when laminating the glass layer 11Lo to become the outer core 11o can be lowered, and the diameter reduction of the glass tube 12T due to heat can be suppressed. Therefore, the variation in the diameter of the glass tube 12T can be suppressed, and the variation in the concentration of the additive added to the glass layers 11Lo and 11Li to become the outer core 11o and the inner core 11i can be suppressed. Therefore, according to the optical fiber 10 of this embodiment, the variation in characteristics can be suppressed.
[0046] In addition, the optical fiber preform 10P of this embodiment includes an inner core glass body 11Pi doped with a rare earth element, an outer core glass body 11Po that tightly surrounds the outer surface of the inner core glass body 11Pi and is not doped with a rare earth element but is doped with germanium and phosphorus, and a cladding glass body 12P that tightly surrounds the outer surface of the outer core glass body 11Po.
[0047] According to such an optical fiber preform, in the same manner as in the description of the optical fiber 10 above, it is possible to manufacture the optical fiber 10 in which deterioration of beam quality and stimulated Raman scattering can be suppressed and the variation in characteristics can be suppressed.
[0048] Although the present invention has been described above by taking the above embodiment as an example, the present invention is not limited to this.
[0049] For example, in the above embodiment, a double-clad fiber has been described as the optical fiber 10, but the optical fiber of the present invention may be a single-clad fiber, or an optical fiber having a clad of three or more layers.
[0050] Furthermore, for example, before the drawing process P4, a jacketing process may be performed in which a clad tube is placed over the base material in order to adjust the ratio between the core diameter and the clad thickness.
[0051] Next, the present invention will be described more specifically with reference to experimental examples.
[0052] (Experimental Example 1) A glass tube made of chlorine-doped quartz with an outer diameter of 32 mm and a wall thickness of 2.5 mm was prepared. Next, while SF6 and O2 were flowing into the quartz tube, the oxyhydrogen burner was traversed seven times so that the temperature of the outer surface of the glass tube reached 2050°C, and the inner surface of the glass tube was cleaned.
[0053] Next, while adjusting the pressure in the through hole of the glass tube to 50 Pa, SiCl4, GeCl4, and POCl3 were supplied together with a carrier gas (O2), and the glass tube was heated by traversing it multiple times with an oxyhydrogen burner to laminate multiple glass layers similar to the glass layer 11Lo shown in FIG. 4, to which germanium and phosphorus were added, on the inner surface of the glass tube, and then collapsed to create an optical fiber preform. Therefore, in this example, the glass layer that becomes the inner core 11i shown in FIG. 5 is not laminated, so that the optical fiber preform does not have an inner core glass body. The glass layer in this optical fiber preform has the same composition as the outer core 11o shown in FIG. 1. In addition, when laminating the glass layers of this example, the carrier gas (O2) to SiCl4 (liquid temperature 24 ° C) was set to 600 sccm, the carrier gas (O2) to GeCl4 (liquid temperature 24 ° C) was changed in the range of 95 to 114 sccm, O2 was set to 1650 sccm, and the carrier gas (O2) to POCl3 was flowed so that the amount of POCl3 generated was in the range of 18 to 50 mg / min, and the glass layers were laminated. Specifically, 48 glass layers were laminated so that the amount of POCl3 generated, the temperature of the outer peripheral surface of the glass tube, the number of glass layers to be laminated, the concentration of P2O5 and GeO2 in the laminated glass layers, and the molar ratio represented by P2O5 / GeO2 were in the order of conditions 1, 2, and 3 in Table 1 below, and the relative refractive index of the laminated glass layers to the glass tube was 0.095 to 0.167%. As described above, the glass tube is made of quartz doped with chlorine. Therefore, if the glass tube is made of pure quartz, the relative refractive index of the laminated glass layers to the glass tube is 0.122 to 0.194%. TIFF0007610999000001.tif61170
[0054] The optical fiber preform thus prepared was stretched thinly, and the relationship between the radial distance from the central axis of the processed optical fiber preform and the dopant concentration was measured. The results are shown in Figure 7. In Figure 7, the dopant concentration at the center is low, but this is due to the dopant volatilizing from the through-hole during collapse.
[0055] The relationship between the radial distance from the central axis of the fabricated optical fiber preform and the refractive index is shown in Figure 8. The optical fiber preform was not stretched during the measurement. As shown in Figure 8, it can be seen that the relative refractive index changes with the change in dopant concentration.
[0056] It was found that by laminating glass layers under the conditions in Table 1, dopants were appropriately added as shown in Figures 7 and 8, and an outer core glass body having a desired relative refractive index could be formed.
[0057] In addition, the change in the outer diameter of the glass tube was measured when stacking the glass layers under the conditions in Table 1. The results are shown in Figure 9. As shown in Figure 9, when stacking glass layers doped with germanium and phosphorus, the outer diameter of the glass tube after stacking a total of 48 layers was approximately 31 mm. Therefore, it was found that the reduction in diameter could be suppressed to approximately 1 mm.
[0058] (Experimental Example 2) A glass tube similar to that of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, POCl3 was not supplied, the carrier gas (O2) for GeCl4 (liquid temperature 24°C) was set to 157-190sccm, the concentration of GeO2 in the glass layer was 1.32mol%, and the relative refractive index to the glass tube was 0.120%. Except for this, 33 glass layers were laminated in the same manner as in Experimental Example 1. In this example, in order to sinter the soot, it was necessary to heat the glass tube with an oxyhydrogen burner so that the temperature of the outer circumferential surface of the glass tube was 2000°C-2050°C. In this example, the outer diameter of the glass tube after laminating 33 glass layers was about 26.4mm. Therefore, the diameter was reduced by about 5.6mm.
[0059] From the results of Experimental Examples 1 and 2, it was found that when only germanium is added without phosphorus when laminating the glass that will become the outer core, the temperature for sintering the soot is high, and therefore the diameter reduction is greater than when germanium and phosphorus are added when laminating the glass that will become the outer core.
[0060] (Experimental Example 3) A glass tube similar to that of the glass tube of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, the pressure in the through hole of the glass tube was adjusted to 85 Pa, the concentration of GeO2 in the glass layer was 1.07 mol%, and the relative refractive index to the glass tube was 0.100%. In this example, it was necessary to heat the glass tube with an oxyhydrogen burner so that the temperature of the outer surface of the glass tube was 2000°C to 2050°C in order to sinter the soot. In this example, the outer diameter of the glass tube after laminating 30 glass layers was about 26.6 mm. Therefore, the diameter was reduced by about 5.4 mm. In addition, due to the pressure in the through hole being set to 85 Pa, there were some parts where the glass tube unnecessarily swelled. Therefore, it was found that when phosphorus is not added and only germanium is added when laminating the glass to be the outer core, it is difficult to control the partial swelling of the glass tube, and therefore it is difficult to suppress the diameter reduction.
[0061] (Experimental Example 4) A glass tube similar to that of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, and 13 glass layers were laminated in the same manner as in Experimental Example 1, except that POCl3 was not supplied, the carrier gas (O2) to GeCl4 (liquid temperature 24°C) was 95 sccm, and the carrier gas (He) to AlCl3 with a raw material temperature of 150°C was 150 sccm. In this example, in order to sinter the soot, it was necessary to heat the glass tube with an oxyhydrogen burner so that the temperature of the outer circumferential surface of the glass tube was 1950°C to 1960°C. In this example, the outer diameter of the glass tube after laminating 13 glass layers was about 32 mm, and the diameter of the glass tube was hardly reduced. However, in this example, the glass tube broke during laminating the 14th glass layer. This is thought to be due to a large difference in thermal expansion coefficient between the glass tube and the glass layer co-doped with germanium and aluminum. Therefore, it was found that phosphorus is more preferable than aluminum as a dopant to be co-doped with germanium.
[0062] (Experimental Example 5) This example is an example of manufacturing an optical fiber preform 10P shown in FIG. 3. A glass tube similar to that of the glass tube of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, the carrier gas (O2) for GeCl4 (liquid temperature 24°C) was set to 83 to 89 sccm, the carrier gas (O2) for POCl3 was flowed so that the amount of POCl3 generated was 42 mg / min, and the concentration of P2O5 in the glass layer was 0.70 mol%, the concentration of GeO2 was 0.67 mol%, and the relative refractive index with respect to the glass tube was 0.120%. Except for this, 18 glass layers that would become the outer core glass body 11Po shown in FIG. 3 were laminated in the same manner as in Experimental Example 1. In this example, in order to sinter the soot, it was necessary to heat the glass tube with an oxyhydrogen burner so that the temperature of the outer peripheral surface of the glass tube was 1950°C. In this example, the outer diameter of the glass tube after laminating 18 glass layers was about 31.7 mm, and the diameter of the glass tube was hardly reduced.
[0063] Next, a glass layer was laminated to become the inner core glass body 11Pi shown in Fig. 3. Specifically, when laminating the glass layers, the pressure in the through hole of the glass tube was adjusted to 50 Pa, the carrier gas (O2) for SiCl4 (liquid temperature 24°C) was set to 600 sccm, the carrier gas (He) for Yb(DPM)3 with a raw material temperature of 230°C was set to 467 to 502 sccm, the carrier gas (He) for AlCl3 with a raw material temperature of 150°C was set to 134 to 137 sccm, and the carrier gas (Ar) for BBr3 with a raw material temperature of 20°C was set to 53 sccm, and the carrier gas (O2) for POCl3 was flowed so that the amount of POCl3 generated was 143 mg / min, and soot deposition, element addition, and sintering were repeated while flowing O2 at 1650 to 3500 sccm and He at 20 to 100 sccm, and lamination was performed. When stacking these glass layers, first, the temperature of the outer surface of the glass tube was traversed to 1630°C to 1650°C while flowing carrier gas of SiCl4, Yb(DPM)3, and AlCl3, then the temperature of the outer surface of the glass tube was traversed to 1200°C while flowing carrier gas of BBr3, then the temperature of the outer surface of the glass tube was traversed to 1200°C while flowing carrier gas of POCl3, and finally the oxyhydrogen burner was traversed to the temperature of the outer surface of the quartz tube to 2050°C. By repeating this, 10 glass layers were stacked. After that, the fire power of the oxyhydrogen burner was further increased and collapsed to produce the optical fiber preform 10P.
[0064] The inner core glass body 11Pi of this optical fiber preform 10P had a diameter of 3.48 mm, the outer diameter of the outer core glass body 11Po was 5.99 mm, and the diameter of the optical fiber preform 10P, i.e., the outer diameter of the cladding glass body 12P, was 17.19 mm. The inner core glass body had a Yb2O3 concentration of 0.29 mol%, a P2O5 concentration of 4.49 mol%, and an Al2O3 concentration of 5.00 mol%.
[0065] (Experimental Example 6) A glass tube similar to that of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, and 18 glass layers to become the outer core were laminated in the same manner as in Experimental Example 2. Next, a glass layer to become the inner core was laminated in the same manner as in Experimental Example 5. Thereafter, the heat of the oxyhydrogen burner was further increased and collapsed to produce an optical fiber preform. The diameter of the inner core glass body of this optical fiber preform was 3.40 mm, the outer diameter of the outer core glass body was 5.88 mm, and the diameter of the optical fiber preform was 16.52 mm.
[0066] The diameter of the optical fiber preform manufactured in Experimental Example 6 was smaller than that of the optical fiber preform manufactured in Experimental Example 5. Therefore, it was found that when the outer core contains phosphorus, the diameter of the manufactured optical fiber preform can be made larger than when the outer core does not contain phosphorus. This is thought to be because, in this example, the diameter of the glass tube is reduced when laminating the glass layer that becomes the outer core compared to Experimental Examples 1 and 5, so that the glass layer laminated later has a smaller total amount of glass per layer in the glass layer laminated in this example than in the glass layers laminated in Experimental Examples 1 and 5.
[0067] (Experimental Example 7) A glass tube similar to that of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, and 21 glass layers were laminated in the same manner as in Experimental Example 2, except that the carrier gas (O2) for GeCl4 (liquid temperature 24°C) was set to 164 to 198 sccm, the concentration of GeO2 in the glass layer was 1.19 mol%, and the relative refractive index to the glass tube was 0.107%. In this example, it was necessary to heat the glass tube with an oxyhydrogen burner so that the temperature of the outer peripheral surface of the glass tube was 2000°C to 2050°C in order to sinter the soot. In this example, the outer diameter of the glass tube after laminating the 21 glass layers was about 28.3 mm, and the glass tube was smaller in diameter than the glass tube after laminating the 18 glass layers that became the outer core glass body 11Po in Experimental Example 5.
[0068] Next, the carrier gas (He) for Yb(DPM)3 at a raw material temperature of 220°C was set to 259 sccm, the carrier gas (He) for AlCl3 at a raw material temperature of 150°C was set to 100 sccm, the carrier gas (O2) for POCl3 was flowed so that the amount of POCl3 generated was in the range of 59 mg / min, He was flowed at 100 sccm, and BBr3 was not used, and five glass layers were laminated in the same manner as in Experimental Example 5. At this time, the temperature of the outer peripheral surface of the glass tube was the same as in Experimental Example 5. After that, the flame power of the oxyhydrogen burner was further increased and collapsed to manufacture an optical fiber preform. The concentration of Yb2O3 in the inner core glass body of the optical fiber preform manufactured under these conditions was 0.21 mol%, the concentration of P2O5 was 3.10 mol%, and the concentration of Al2O3 was 3.22 mol%.
[0069] (Experimental Example 8) A glass tube similar to that of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, and the carrier gas (O2) for GeCl4 (liquid temperature 24°C) was set to 153 to 198 sccm, and the concentration of GeO2 in the glass layer was set to 1.17 mol%, but other than that, 28 glass layers to become the outer core glass body were laminated in the same manner as in Experimental Example 7. At this time, the temperature of the outer peripheral surface of the glass tube was the same as in Experimental Example 7.
[0070] Next, five glass layers were laminated in the same manner as in Experimental Example 7, except that the carrier gas (He) for AlCl3 at a raw material temperature of 150°C was set to 120 sccm. At this time, the temperature of the outer peripheral surface of the glass tube was the same as in Experimental Example 5. Thereafter, the flame power of the oxyhydrogen burner was further increased and collapsed to produce an optical fiber preform. The optical fiber preform produced under these conditions had an inner core glass body with a Yb2O3 concentration of 0.16 mol%, a P2O5 concentration of 2.29 mol%, and an Al2O3 concentration of 2.82 mol%.
[0071] The concentration of Yb2O3 in the inner core glass body of Experimental Example 8 was lower than that of the inner core glass body of Experimental Example 7. It is believed that the change in the flow rate of the carrier gas to AlCl3 has almost no effect on this result, and the reason for this result is that the number of glass layers to become the outer core glass body is greater in Experimental Example 8 than in Experimental Example 7. Specifically, the distance from the outer peripheral surface of the glass tube to the glass layer to be laminated when laminating the glass layer to become the inner core glass body is greater in Experimental Example 8 than in Experimental Example 7, so that the temperature transmitted to the laminated glass layer is lower. Therefore, when the glass tube is reduced in diameter and the thickness of the glass tube is increased when laminating the glass layer to become the outer core glass body, the temperature transmitted to the glass layer to be laminated when laminating the glass layer to become the inner core glass body is lower, and it is expected that the concentration of Yb2O3 added to the glass layer tends to be lower.
[0072] (Experimental Example 9) Six glass tubes similar to the glass tube of Experimental Example 1 were prepared, and each glass tube was cleaned in the same manner as in Experimental Example 1, and 18 glass layers were laminated in the same manner as in the lamination of the glass layers that would become the outer core glass body of Experimental Example 5. Therefore, germanium and phosphorus were added to these glass layers. Then, the outer diameter of each glass tube was measured. The results are shown in Figure 10. The average outer diameter was 30.7 mm, and the standard deviation of the outer diameter was 0.18.
[0073] (Experimental Example 10) Six glass tubes similar to those in Experimental Example 1 were prepared, and each glass tube was cleaned in the same manner as in Experimental Example 1. 18 glass layers were laminated in the same manner as in the lamination of the glass layers that would become the outer core glass body in Experimental Example 3. Therefore, no phosphorus was added to this glass layer, and only germanium was added. After that, the outer diameter of each glass tube was measured. The results are shown in Figure 10. The average outer diameter was 26.8 mm, and the standard deviation of the outer diameter was 0.39.
[0074] The results of Experimental Examples 9 and 10 showed that when germanium and phosphorus are co-doped into the glass layer that becomes the outer core glass body, the glass tube shrinks in diameter significantly and the outer diameter of the glass tube varies compared to when no phosphorus is added to the glass layer that becomes the outer core glass body but only germanium is added.
[0075] (Experimental Example 11) A glass tube similar to that of the glass tube of Experimental Example 1 was cleaned in the same manner as in Experimental Example 1, the carrier gas (O2) for GeCl4 (liquid temperature 24°C) was set to 75 to 84 sccm, the carrier gas (O2) for POCl3 was flowed so that the amount of POCl3 generated was in the range of 45 mg / min, and the concentration of P2O5 in the laminated glass layers was adjusted to 0.73 mol%, the concentration of GeO2 was adjusted to 0.60 mol%, and the relative refractive index to the glass tube was adjusted to 0.120%, and 23 glass layers were laminated in the same manner as in Experimental Example 1. The molar ratio of P2O5 / GeO2 in this glass layer was 1.21. After that, the fire power of the hydrogen burner was further increased and collapsed to produce an optical fiber preform. In this example, the concentration of P2O5 added to the glass layer was higher than that of conditions 2 and 3 of Experimental Example 1, so that the temperature of the outer surface of the glass tube when laminating the glass layers could be made lower than the temperature of the outer surface of the glass tube under conditions 2 and 3 of Experimental Example 1. [Industrial Applicability]
[0076] According to the present invention, there are provided an optical fiber capable of suppressing deterioration of beam quality and suppressing characteristic variations even when the effective cross-sectional area of light is large, and an optical fiber preform used therefor, which can be used in fields such as fiber lasers. [Explanation of symbols]
[0077] 10. Optical fiber 10N Bare optical fiber 10P···Optical fiber base material 11. Core 11i...Inner core 11 Outer core 11Pi...Inner core glass body 11Po...Outer core glass body 12. Inner cladding 12P... Clad glass body
Claims
1. an inner core doped with a rare earth element; an outer core that surrounds the outer peripheral surface of the inner core without any gaps and is doped with germanium and phosphorus but not doped with rare earth elements; a cladding that tightly surrounds an outer peripheral surface of the outer core; Including, the inner core is co-doped with ytterbium and phosphorus; The concentration of phosphorus added to the inner core is greater than the concentration of phosphorus added to the outer core.
1. An optical fiber comprising:
2. The outer core is free of dopants other than germanium and phosphorus.
2. The optical fiber according to claim 1 .
3. P in the outer core 2 O 5 / GeO 2 The molar ratio represented by is 1.21 or less.
3. The optical fiber according to claim 1 or 2.
4. a rare earth doped inner core glass body; an outer core glass body that surrounds the outer peripheral surface of the inner core glass body without any gaps and is doped with germanium and phosphorus but not doped with rare earth elements; a cladding glass body that tightly surrounds the outer peripheral surface of the outer core glass body; Including, the inner core glass body is co-doped with ytterbium and phosphorous; The concentration of phosphorus added to the inner core glass body is greater than the concentration of phosphorus added to the outer core glass body.
1. An optical fiber base material comprising:
Citation Information
Patent Citations
Manufacture of optical fiber and base material for said optical fiber
JP1986059404A
Optical fiber
JP1989145881A
Light amplifying optical fiber and manufacture thereof
JP2000252558A
Thulium doped fiber configuration for enhanced high power operation
US20090074013A1
Active element-added optical fiber, resonator, and fiber laser device
WO2020203900A1